Assessing the readiness of mobile construction organizations for project execution - Oleynik, Pavel; Kazaryan, Ruben; Doroshin, Ivan; Avetisyan, Robert (Edelweiss Applied Science and Technology, 2025)
Active development of remote hard-to-reach areas obliges construction organizations to significantly increase the mobility of their units, capable of autonomously functioning in difficult natural and climatic conditions. For these units to perform production and public utilities functions, appropriate labor and material and technical resources are required. At the same time, almost every job can be performed by various combinations of resources, the options of which differ from each other in technical and economic indicators. The development of such options depends on the type and conditions of the facility construction, the level of specialization and concentration of resources, the availability of these resources, etc. In this regard, the principle of resource substitutability is especially significant for mobile units the proficiency of workers in related trades, the creation of sets with various means of technical equipment for teams. To select resources for mobile units, a scheme for assessing the readiness of a construction organization for work execution is proposed, which provides an assessment for each brigade and an overall assessment of the construction organization. At the final stage of assessment, integral parameters are established separately for labor resources and technical means of their equipment.